Ubiquitous cell-surface glycoprotein on tumor cells is proliferation-associated receptor for transferrin. - Sutherland, R (1981)
A murine monoclonal antibody (OKT9) raised against human leukemic cells binds to a wide variety of leukemia and tumor cell lines and to a minority of leukemia cells taken directly from patients. Fetal thymus and liver are strongly reactive as are some normal, immature hemopoietic cells and activated lymphocytes. Reactivity with OKT9 appears to correlate with proliferation status in both normal and malignant populations. Biochemical analysis indicates that this structure is a approximately equal to 180,000-dalton glycoprotein with two disulfide-bonded subunits of approximately equal to 90,000-daltons. Isolation of the transferrin receptor from a T-cell line (MOLT-4) indicates that it also has a dimeric approximately equal to 180,000-dalton structure. Radio-labeled transferrin bound to its receptors can be specifically precipitated by the monoclonal OKT9, although the latter does not bind transferrin itself, indicating that the antigenic structure defined by this antibody is likely to be the transferrin receptor.